2019
DOI: 10.3390/urbansci3040114
|View full text |Cite
|
Sign up to set email alerts
|

Promoting and Demoting Factors of Ecodesign Methodologies for The Application of Recycled Construction Waste: A Case Study of a Composite Product

Abstract: Thermoplastic composites manufacturing could be a potential end-of-life option for separated construction and demolition waste. This study aims to find out how well the established ecodesign methodologies support the choice of recycled composite materials in new product design, and what challenges these materials offer to the designer. A product design case study was conducted by applying the ecodesign methodologies Environmental Quality Function Deployment and Technique for Order of Preference by Similarity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Only a few RCMs find their way into qualified product lists and Thompson et al (2010) claim this to be a reason for the lack of awareness regarding RCMs. In the same vein, Sormunen and Kärki (2019) emphasized that information about RCMs is not readily available through material databanks, which makes designing with RCMs complicated. Alternatively, information about virgin construction materials is easily accessible and therefore, material specifiers tend to go for virgin materials which makes design processes less complex ( Sormunen and Kärki, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few RCMs find their way into qualified product lists and Thompson et al (2010) claim this to be a reason for the lack of awareness regarding RCMs. In the same vein, Sormunen and Kärki (2019) emphasized that information about RCMs is not readily available through material databanks, which makes designing with RCMs complicated. Alternatively, information about virgin construction materials is easily accessible and therefore, material specifiers tend to go for virgin materials which makes design processes less complex ( Sormunen and Kärki, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to Nußholz et al (2019) , information on the durability and resource-saving potentials of RCMs are likewise limited. Construction actors are not aware of the economics of using RCMs as well ( Sormunen and Kärki, 2019 ). For example, Correia et al (2021) highlight that builders are not aware of financial benefits such as tax reductions that can be gained through the use of RCMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourier transform infrared spectroscopy (FTIR) studies are a technique that is based on the interaction of electromagnetic radiation in the thermal infrared region; it measures different types of vibrations between atoms according to their atomic bonds and allows the distinction of the bands associated with functional groups of interest in the spectra generated [11][12][13][14]. In similar studies to the proposed work, FTIR has shown that coconut fiber has absorption peaks in its IR spectrum at 1741 and 1511 cm −1 , corresponding to the conjugated stretch C = O of hemicellulose aldehyde and ester, absorption at 1332 cm −1 of C-H in the flat deformation of cellulose rings, bands in 1038 cm −1 of C-O groups of hemicellulose, cellulose, and C-H (lignin deformation), and stretch for the cellulose glucose ring structure at 897 cm −1 [15].…”
Section: Introductionmentioning
confidence: 99%